A City Cannot Be a Work of Art Learning Economics and Social Theory From Jane Jacobs - Ikeda, Sanford (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
"Jane Jacobs is best known for her impact on how people view and plan cities. But she considered her economic writing her most important. Few people focus on her economics. Sanford Ikeda does it thoroughly and with great insight and is a rare voice in this area. Thus, this work is a very important addition to the application of Jacobs' thinking." -Roberta Brandes Gratz, Award-winning journalist and urbanist, Author of The Battle for Gotham. "This book is original both in revisiting Jane Jacobs's thought and in freshly contributing to urban studies, urban economics and planning theory. I believe it is the best critical presentation of Jacobs's work ever written." -Stefano Moroni, Professor of Planning, Polytechnic University of Milan. This open access book connects Jane Jacobs's celebrated urban analysis to her ideas on economics and social theory. While Jacobs is a legend in the field of urbanism and famous for challenging and profoundly influencing urban planning and design, her theoretical contributions - although central to her criticisms of and proposals for public policy - are frequently overlooked even by her most enthusiastic admirers. This book argues that Jacobs's insight that "a city cannot be a work of art" underlies both her ideas on planning and her understanding of economic development and social cooperation. It shows how the theory of the market process and Jacobs's theory of urban processes are useful complements - an example of what economists and urbanists can learn from each other. This Jacobs-cum-market-process perspective offers new theoretical, historical, and policy analyses of cities, more realistic and coherent than standard accounts by either economists or urbanists. Sanford Ikeda is Professor Emeritus at Purchase College, The State University of New York, a fellow of the Colloquium on Market Institutions and Economics Processes at New York University, and serves on the boards of The Economic Freedom Institute, Cosmos+Taxis, and The Center for the Living City. He is the author of Dynamics of the Mixed Economy (1997). His research focuses on the interconnections among cities, spontaneous social orders, entrepreneurial development, and urban policy.